Human Adipose Mesenchymal Stem Cells Show More Efficient Angiogenesis Promotion on Endothelial Colony-Forming Cells than Umbilical Cord and Endometrium - Haiyuan Lu; Fan Wang; Hua Mei; Siqi Wang; Lamei Cheng (Stem Cells International)
Angiogenesis is a complicated process in which perivascular cells play important roles. Multipotent mesenchymal stem/stromal cells (MSCs) from distinct tissues have been proved to be proangiogenic and share functional properties and gene expression profiles with perivascular cells. However, different tissues derived MSCs may exhibit different potential for clinical applications. Accordingly, comparative studies on different MSCs are essential. Here, we characterized MSCs from adipose (ADSCs), umbilical cord (UCMSCs), and endometrium (EMSCs) in terms of the surface antigen expression, differentiation ability, and the ability of angiogenesis promotion on endothelial colony-forming cells (ECFCs) both in vitro and in vivo. No significant differences in immunophenotype and differentiation were observed. In addition, three types of MSCs all located around tubular-like structures formed by ECFCs in coculture system on matrigel. But ECFCs seeded on ADSCs monolayer formed more organized capillary-like network than that on UCMSCs or EMSCs. When suspended with ECFCs in matrigel and implanted into nude mice, ADSCs promoted more functional vessel formation after 7 days. Moreover, in murine hindlimb ischemia model, cotransplantation of ECFCs with ADSCs was significantly superior to UCMSCs and EMSCs in promoting perfusion recovery and limb salvage. Furthermore, ADSC-conditioned medium (CM) contained more proangiogenic factors (such as vascular endothelial growth factor-A, platelet-derived growth factor BB, and basic fibroblast growth factor) and less inhibitory factor (such as thrombospondin-1), when compared with UCMSC-CM and EMSC-CM. And ADSC-CM more durably stabilized the vascular-like structures formed by ECFCs on matrigel and promoted ECFCs migration more efficiently. In summary, MSCs from adipose show significantly efficient promotion on angiogenesis both in vitro and in vivo than UCMSCs and EMSCs. Hence, ADSCs may be recommended as a more suitable source for treating hindlimb ischemia.